2020
DOI: 10.1111/anae.15180
|View full text |Cite
|
Sign up to set email alerts
|

Resilience strategies to manage psychological distress among healthcare workers during the COVID‐19 pandemic: a narrative review

Abstract: Summary The COVID‐19 pandemic marks an extraordinary global public health crisis unseen in the last century, with its rapid spread worldwide and associated mortality burden. The longevity of the crisis and disruption to normality is unknown. With COVID‐19 set to be a chronic health crisis, clinicians will be required to maintain a state of high alert for an extended period. The support received before and during an incident is likely to influence whether clinicians experience psychological growth or injury. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
368
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(440 citation statements)
references
References 56 publications
13
368
0
15
Order By: Relevance
“…Notably, in phase 1 of the pandemic, Italian health workers suffered from a lack of clear and specific intervention protocols, both in operational and pharmacological terms, as well as difficulties with reorganizing departments, a lack of necessary equipment, and little knowledge about the characteristics of the virus. The extent of these difficulties in the first phase of the pandemic may have limited the externalization of individual resources so that the results seem to reveal an absence of significance or protective efficacy of other coping strategies, such as focused problem and support, which normally tend to be more functional in interventions by rescuers, especially in the long term [57,60,69].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Notably, in phase 1 of the pandemic, Italian health workers suffered from a lack of clear and specific intervention protocols, both in operational and pharmacological terms, as well as difficulties with reorganizing departments, a lack of necessary equipment, and little knowledge about the characteristics of the virus. The extent of these difficulties in the first phase of the pandemic may have limited the externalization of individual resources so that the results seem to reveal an absence of significance or protective efficacy of other coping strategies, such as focused problem and support, which normally tend to be more functional in interventions by rescuers, especially in the long term [57,60,69].…”
Section: Discussionmentioning
confidence: 98%
“…Heath at al. [69] investigated the mediating role of coping strategies and resilience to stress during a pandemic as well as the importance of increasing these factors in healthcare workers to mitigate or minimize potential adverse psychological effects. Most studies have analyzed the predictive and mediating effect of coping strategies and hardiness [65][66][67] singularly; few studies have analyzed the relationships between resilience, coping strategies, and mental health in healthcare and emergency workers [57,70].…”
Section: Mediating Role Of Hardiness and Coping On Mental Health In Hmentioning
confidence: 99%
“…Our study found that on an individual level, personal health and ability to pursue self-care activities influenced their positive and negative experiences. Similarly, a review of resiliency strategies to promote HW wellbeing during pandemics concluded that promoting HWs’ ability to practice self-care on an individual level, including physical activity, sleep hygiene, and mindfulness, can foster their resiliency and decrease their psychological distress [ 32 ]. Providing HWs with resources and time to practice self-care activities and rest is vital to promote wellbeing during the COVID-19 pandemic and future outbreaks [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The virus is spreading very quickly and efficiently so that many regions are increasing intensive care beds, revolutionizing entire hospital wards. Our healthcare professionals are facing disease pulling 12-h shifts in critical situations and this phenomenon is leading to serious psychological distress in this population here ( Anmella et al, 2020 ; Barello et al, 2020 ; De Giorgio, 2020 ; ISS, 2020 ; Ramaci et al, 2020a ) as well as in other countries ( Bohlken et al, 2020 ; Heath et al, 2020 ; Ornell et al, 2020 ; Tsamakis et al, 2020 ).…”
mentioning
confidence: 99%